The effect of Omani-Iranian relations on the security of the Gulf Cooperation Council countries after the Arab Spring. Issue 3 (2nd July 2016) - Al-Bolushi, Maryam
ABSTRACT: This research paper focuses on Gulf–Iran relations within the framework of the bilateral relationship between Oman and Iran. This relationship is unique as well as distinct from Oman's relations with the other nations of the Gulf Cooperation Council (GCC) and has a direct influence on Gulf regional security. Oman's relationship with Iran has grown stronger and firmer after the events of the Arab Spring. This comes at a time when the Gulf countries are suffering worsening internal security, political and economic conditions and disagree amongst themselves about how to deal with Iran. Hence, the Omani-Iranian rapprochement is intensifying the security anxieties of the GCC countries. This paper examines the conceptual frameworks for security and cooperation within the GCC. Oman's view on security and cooperation is seen in its foreign policy which adheres to non-intervention and neutrality in foreign affairs. Omani-Iranian relations are analyzed in how they affect Gulf integration and the role played by Oman in the Iranian nuclear deal. The paper concludes by discussing Oman's position on the current conflict in Yemen and its effect on Gulf security as well as Oman's role in mediation between the parties in the conflict.